Pengalaman Komunikasi Pekerja Seks Komersial di Kabupaten Bekasi : (Studi Fenomenologi Tentang Pengalaman Komunikasi PSK di Kabupaten Bekasi) - Inzaghi Muharram, Muhammad; Nur Iman, Asrul (JAMBURA JURNAL ILMU KOMUNIKASI, 2024)
Communication Experiences of Commercial Sex Workers in Bekasi Regency (Phenomenological Study of the Communication Experiences of Commercial Sex Workers in Bekasi Regency. The aim of this research is to find out the communication experiences of someone who works as a Commercial Sex Worker, especially in the Bekasi Regency area and to find out the motives someone works as a commercial sex worker. This research uses Alfred Schutz's phenomenological theory and qualitative methods by collecting data through interviews, observation and documentation. The informants in this research are four people who work as prostitutes, consisting of two people in the Cibitung area and two. people in the Cikarang area. The result of this research is that the pleasant communication experience experienced by Commercial Sex Workers in Bekasi Regency was that they were given TIP from "customers". The unpleasant communication experience experienced by Commercial Sex Workers in Bekasi Regency is that they often receive physical violence perpetrated by "customers" who are under the influence of alcohol. The motive behind the informants in this study working as prostitutes was economic factors.